High-normal liver enzyme levels in early pregnancy predispose the risk of gestational hypertension and preeclampsia: A prospective cohort study - Zhang, Yi; Sheng, Chen; Wang, Dingmei; Chen, Xiaotian; Jiang, Yuan; Dou, Yalan; Wang, Yin; Li, Mengru; Chen, Hongyan; He, Wennan; Yan, Weili; Huang, Guoying (Frontiers in Cardiovascular Medicine, 2022)
Background: Gestational hypertension (GH) and preeclampsia (PE) are severe adverse gestational complications. Previous studies supported potential link between elevated liver enzyme levels and GH and PE. However, given the transient physiological reduction of liver enzyme levels in pregnancy, little is known whether the associations of the high-normal liver enzyme levels in early pregnancy with GH and PE exist in pregnant women. Methods: Pregnant women in this study came from a sub-cohort of Shanghai Preconception Cohort, who were with four liver enzyme levels examined at 9-13 gestational weeks and without established liver diseases, hypertension and preeclampsia. After exclusion of pregnant women with clinically-abnormal liver enzyme levels in the current pregnancy, associations of liver enzyme levels, including alkaline phosphatase (ALP), alanine transaminase (ALT), aspartate aminotransferase (AST) and gamma-glutamyl transpeptidase (GGT), with GH and PE status were assessed by multivariable log-binomial regression. Population attributable fraction was measured to estimate the fractions of GH and PE that were attributable to the high-normal liver enzyme levels. Results: Among 5,685 pregnant women 160 (2.8%) and 244 (4.3%) developed GH and PE, respectively. After adjustment for potential covariates, higher ALP, ALT and GGT levels were significantly associated with the risk of GH (adjusted risk ratio (aRR) :1.21 [95% confidence interval, 1.05-1.38]; 1.21 [1.05-1.38]; and 1.23 [1.09-1.39]), as well as the risk of PE(1.21 [1.13-1.29]; 1.15 [1.03-1.28]; 1.28 [1.16-1.41]), respectively. The cumulative population attributable fraction of carrying one or more high-normal liver enzyme levels (at 80th percentile or over) was 31.4% for GH and 23.2% for PE, respectively.